Handbook of Positive Psychology, Religion, and Spirituality - Davis, Edward B.; Worthington Jr., Everett L.; Schnitker, Sarah A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access handbook aims to bridge the gap between the fields of positive psychology and the psychology of religion and spirituality. It is the authoritative guide to the intersections among religion, spirituality, and positive psychology and includes the following sections: (1) historical and theoretical considerations, (2) methodological considerations, (3) cultural considerations, (4) developmental considerations, (5) empirical research on happiness and well-being in relation to religion and spirituality, (6) empirical research on character strengths and virtues in relation to religion and spirituality, (7) clinical and applied considerations, and (8) field unification and advancement. Leading positive psychologists and psychologists of religion/spirituality have coauthored the chapters, drawing on expertise from their respective fields. The handbook is useful for social and clinical scientists, practitioners in helping professions, practitioners in religious and spiritual fields, and students of psychology and religion/spirituality. A comprehensive resource examining the intersections of positive psychology and the psychology of religion/spirituality Draws connections between two fields that research has increasingly shown to be connected (3z(BThis Handbook provides a masterful, comprehensive review of theory, research, and clinical applications at the exciting intersection between the psychology of religion/spirituality and positive psychology. It demonstrates each of those fields is incomplete without the other. This book should be in the shelf of every serious student of religion, spirituality, and psychology.(3y (B-Pehr Granqvist, Ph.D., Professor of Psychology, Stockholm University, Author of Attachment in Religion and Spirituality: A Wider View (3z(BWithin this volume is found the next frontier of positive psychology, exponentially expanded through spiritual awareness and the translation of spiritual experience into lived positive cognition, behavioral habit, and practice. The editors of this volume help clear a rich new terrain for the next generation of humanitarian practitioners, researchers, and scholars.(3y (B-Lisa Miller, Ph.D., Professor of Psychology and Education, Teachers College, Columbia University, Editor of Oxford University Press Handbook of Psychology and Spirituality, Author of The Awakened Brain and The Spiritual Child (3z(BAt last! This broad-based, creative, integrative handbook helps fill a niche by focusing directly on the interface between positive psychology and the psychology of religion and spirituality.(3y (B-Julie J. Exline, Ph.D., Professor of Psychology, Department of Psychological Sciences, Case Western Reserve University, Co-Author of Working With Spiritual Struggles in Psychotherapy: From Research to Practice.s
Part I: Historical and Theoretical Considerations -- Integrating Positive Psychology and the Psychology of Religion and Spirituality: Transcending Coexistence to Potentiate Coevolution -- Positive Psychology and the Psychology of Religion and Spirituality in Historical Perspective -- On the Integration of Positive Psychology and the Psychology of Religion and Spirituality: Logical, Normative, and Methodological Questions -- Virtues in Positive Psychology and the Psychology of Religion and Spirituality -- Theories of Health and Well-Being Germane to a Positive Psychology of Religion and Spirituality -- Meaning as a Framework for Integrating Positive Psychology and the Psychology of Religiousness and Spirituality -- Part II: Methodological Considerations -- Measurement at the Intersection of Positive Psychology and the Psychology of Religion and Spirituality -- Methodological Diversity in Positive Psychology and the Psychology of Religion and Spirituality -- Part III: Cultural Considerations.-Cultural Considerations in Positive Psychology and the Psychology of Religion and Spirituality -- Positive Psychology and Christianity -- Positive Psychology and Judaism -- Living the Good Life: An Islamic Perspective on Positive Psychology -- Positive Psychology and Hinduism -- Positive Psychology and Buddhism -- "Positive Psychology and Religion/Spirituality Across Cultures in Europe, Non-U.S. North America, and South America" -- Positive Psychology and Religion/Spirituality Across Cultures in Africa, Asia, and Oceania -- Part IV: Developmental Considerations -- Religion, Spirituality, and Youth Thriving: Investigating the Roles of the Developing Mind and Meaning-Making -- Religious/Spiritual Development and Positive Psychology: Toward an Integrative Theory -- Part V: Happiness and Well-Being -- The Scientific Study of Life Satisfaction and Religion/Spirituality -- The Scientific Study of Positive Emotions and Religion/Spirituality -- The Scientific Study of Positive Psychology, Religion/Spirituality, and Physical Health -- The Scientific Study of Positive Psychology, Religion/Spirituality, and Mental Health -- Part VI: Character Strengths and Virtues -- The Scientific Study of Religion/Spirituality, Forgiveness, and Hope -- Religion/Spirituality and the Twin Virtues of Humility and Gratitude -- Theological Virtues, Health, and Well-Being: Theory, Research, and Public Health -- Part VII: Clinical and Applied Considerations -- Integrating Positive Psychology, Religion/Spirituality, and a Virtue Focus Within Culturally Responsive Mental Healthcare -- Meaningfulness and Religious/Spiritual Meaning Systems at Work: A Multilevel Framework -- Positive Psychology and Religiousness/Spirituality in the Context of Couples and Families -- Positive Psychology in the Context of Religious Communities -- Building Spiritual Fortitude and Resilience Following Disaster: Synthesizing the Contributions of Positive Psychology and Religion/Spirituality -- Part VIII: Field Unification and Advancement -- Future Directions for the Positive Psychology of Religion and Spirituality.
Keywords: Positive psychology; Psychology and religion; Positive Psychology; Psychology of Religion and Spirituality